2006
DOI: 10.1111/j.1532-849x.2006.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Dentist Communication with the Dental Laboratory for Prosthodontic Treatment Using Implants

Abstract: Most laboratories working on implant prosthodontic cases report inadequate communication between the laboratory and dentists related to materials and techniques used in fabrication of implant restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…Lynch & Allen (2005) (22) examined the quality of communication for fixed prosthodontics in Ireland and found that 55% of written instructions provided were poor or contained no design instruction. Similar inadequate communication has been documented in relation to implants (37). The reasons for inadequate communication by general dental practitioners have historically been attributed to financial and/or educational issues.…”
Section: Discussionsupporting
confidence: 76%
“…Lynch & Allen (2005) (22) examined the quality of communication for fixed prosthodontics in Ireland and found that 55% of written instructions provided were poor or contained no design instruction. Similar inadequate communication has been documented in relation to implants (37). The reasons for inadequate communication by general dental practitioners have historically been attributed to financial and/or educational issues.…”
Section: Discussionsupporting
confidence: 76%
“…The evidence presented here indicates that our IPE curriculum is somewhat effective in addressing concerns around communication and collaboration -issues that have been extensively raised in the literature (14,17,19). Some dentistry students saw little value in 'sitting alongside' dental technology students.…”
Section: Discussionmentioning
confidence: 80%
“…A technician receives a prescription (work authorisation) from a dentist, dental prosthetist or dental specialist regarding the fabrication or repair of an oral prosthesis (14). The dental technician uses his/her theoretical and practical knowledge to determine appropriate materials, design, construction techniques and positioning of various components to meet the patient's needs for restoration of function and aesthetics (15).…”
Section: The Dental Technicianmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Technician involvement at the planning stages of a proposed restoration that requires a gingival component has been recommended. 31 Where ridge lap design is critical for aesthetics, technician input is important to produce an aesthetic and cleansable result.…”
Section: Technician-clinician Interfacementioning
confidence: 99%